Досвід упровадження освітньої компоненти, що формує інклюзивну компетентність майбутніх учителів закладів загальної середньої освіти - Кузава, Ірина Борисівна (КОГПА імені Т.Г. Шевченка, 2024)
У статті розкрито досвід упровадження освітньої компоненти, що формує інклюзивну компетент-ність майбутніх фахівців закладів загальної середньої освіти. Зазначено, що актуальним на етапі впро-вадження інклюзивної освіти як успішного фактору управління навчально-виховним процесом закладів загальної середньої освіти є формування інклюзивної компетентності майбутніх учителів географії, ін-форматики, математики, природничих наук, фізики, хімії, біології, фізичної культури, викладачів фахової передвищої освіти інтегрованих навчальних курсів природничої галузі як невід’ємної умови функціонування сучасної системи загальної середньої освіти.У ході дослідження виявлено, що інклюзивна компетентність майбутніх фахівців закладів загальноїсередньої освіти є інтегральною професійно-особистісною характеристикою, яка включає не лише теоре-тичну й практичну готовність до ефективного виконання професійних функцій, а й такі суб’єктивні якос-ті особистості, як активність, самостійність, відповідальність, комунікативність, емоційну гнучкість.За результатами аналізу результатів дослідження встановлено, що формування інклюзивної компе-тентності майбутніх учителів закладів загальної середньої освіти передбачає введення в зміст освітніх програм спеціальності 014 «Середня освіта» відповідної освітньої компоненти й/або інтеграції окремих змістових модулів до наявних ОК. На нашу думку, це сприятиме формуванню професійної компетентності майбутніх фахівців середньої освіти з урахуванням інклюзивного компонента, забезпечить належну про-фесійну підготовку до роботи в умовах інклюзії
Introduction. The article reveals the experience of implementing educational components that form the inclusive competence of future specialists of general secondary education institutions. It is noted that the formation of inclusive competence of future teachers of geography, informatics, mathematics, natural sciences, physics, chemistry, biology, physical culture, teachers of professional pre-university education is relevant at the stage of implementation of inclusive education as a successful factor in managing the educational process of general secondary education institutions education of integrated educational courses in the field of natural sciences as an integral condition for the functioning of the modern system of general secondary education.Purpose: consists in revealing the experience of implementing educational components that form the inclusive competence of future specialists of general secondary education institutions in the process of their professional readiness for practical work in conditions of inclusion.Methods: general scientific and psychological-pedagogical methods: theoretical-informational, practical-active, search-creative, methods of organizing independent work, monitoring and evaluation, as well as non-traditional teaching methods. In particular: verbal (conversation, story, explanation, dispute); visual (demonstration, illustration); practical (exercise, practical work); induction, deduction; translation; explanatory and illustrative, reproductive, problem statement, partially research, research; methods of mastering knowledge, formation of abilities and skills, application of acquired knowledge, abilities and skills; interactive methods, etc.Originality: on the basis of a theoretical and practical study of the current state of inclusive education in Ukraine, to determine and substantiate and reveal the experience of implementing educational components that form the inclusive competence of future specialists of general secondary education institutions.Results. In the course of the study, it was found that the inclusive competence of future specialists of general secondary education institutions is an integral professional and personal characteristic, which includes not only theoretical and practical readiness for the effective performance of professional functions, but also such subjective personality qualities as activity, independence, responsibility, communicativeness, emotional flexibility.Conclusion. According to the results of the analysis of the results of the study, it was established that the formation of inclusive competence of future specialists of general secondary education institutions involves the introduction of relevant educational components into the content of educational programs and/or the integration of individual content modules into existing OCS. In our opinion, this will contribute to the formation of professional competence of future specialists of secondary education, taking into account the inclusive component, and will ensure proper professional training for work in conditions of inclusion
Keywords: інклюзивна компетентність; спеціальна освіта; освітній компонент; майбутні вчителі закладів загальної середньої освіти; освітня програма; Спеціальна освіта; 378.016:376]:373.3/.5.011.3-051